2016
DOI: 10.1515/med-2016-0043
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of VHL and Jade-1 gene expression in human renal cell carcinoma

Abstract: AbstractObjectiveThe aim of this study was to investigate the correlation of von Hippel-Lindau tumor suppressor (VHL) mRNA expression and jade family PHD finger 1 (Jade-1) gene expression in patients with renal cell carcinoma (RCC). Another aim of this study was to analyze the relationship of these two genes with clinicalpathological features of the RCC patients. Methods: A total of 75 RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
(19 reference statements)
2
8
0
Order By: Relevance
“…Although in the present study, a decreased VHL mRNA level was observed in tumor samples, this was not found to be associated with the clinicopathological data of the patients or with their outcome or sunitinib treatment. Similar to our results, Xiao-Fen et al reported the underexpression of VHL mRNA in tumor samples from 75 RCC patients (the number of ccRCC cases was not specified) in comparison to normal kidney tissues (23). However, in contrast to our findings, Xiao-Fen et al observed that this decreased expression was associated with cancer TNM progression and tumor size, although the lack of data on the histological subtypes of RCC precludes a direct comparison between their results (23) and ours.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although in the present study, a decreased VHL mRNA level was observed in tumor samples, this was not found to be associated with the clinicopathological data of the patients or with their outcome or sunitinib treatment. Similar to our results, Xiao-Fen et al reported the underexpression of VHL mRNA in tumor samples from 75 RCC patients (the number of ccRCC cases was not specified) in comparison to normal kidney tissues (23). However, in contrast to our findings, Xiao-Fen et al observed that this decreased expression was associated with cancer TNM progression and tumor size, although the lack of data on the histological subtypes of RCC precludes a direct comparison between their results (23) and ours.…”
Section: Discussionsupporting
confidence: 91%
“…The deregulation of the VHL gene in ccRCC has been widely reported (5,22,23). Studies on the expression patterns of HIF1A (24-28), HIF2A (25-28), VEGFA (5,24,27-29) and P53 (30,31) in ccRCC have revealed variations in terms of cancer progression and/or patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several biomarkers for KIRC that have been detected include von Hippel-Lindau (VHL) [ 8 11 ], vascular endothelial growth factor (VEGF) [ 12 15 ], carbonic anhydrase IX (CAIX) [ 16 18 ], and hypoxia-inducible factor 1 alpha/2 alpha (HIF1a/2a) mutations [ 19 21 ], some of which were able to forecast the medical effectiveness and outcomes. Despite that, there have been scarce studies into the molecular biomarkers of KIRP for the prediction of therapeutic efficacy and prognostication.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, VHL deficient ccRCC cells prompted β-catenin-driven transcription of AURKA, which was associated with the deformation of primary cilia and induced renal oncogenesis [88]. In sporadic ccRCC, the expression of VHL and JADE-1 was lower; however, in normal conditions, pVHL stabilized JADE-1 that negatively regulated Wnt/β-catenin and promoted apoptosis and renal tumor suppression [89,90].…”
Section: Impact Of Vhl and Hypoxia On Wnt/-catenin Pathway In Ccrccmentioning
confidence: 99%